ANALYSING EFFICIENCY OF AGGRESSIVE ETF-COMPOSED PORTFOLIO STRATEGIES - A. Zaviyalov (Vestnik MGIMO-Universiteta)
The article investigates investment characteristics of Exchange Traded Funds, a unique category of mutual funds which can be traded like any common equity on any stock exchange through authorized broker companies. One can buy and sell ETFs during the entire trading session, one can open short positions using ETFs and trade on margin. ETF price is determined by supply and demand and due to arbitrage, prices are very close to net asset values (NAV). ETFs attract both individual and institutional investors because they combine the benefits of open-end and closed-end funds. The article explores the results of statistical research to find a principal opportunity to implement an "aggressive" ETF-composed portfolio strategy which can secure stable above-market returns. To put it otherwise, the research aims to test the market efficiency hypothesis in the sector of ETF-composed portfolios. The research methodology centers on statistically testing the null hypothesis whether the average S&P500 return and each of the ETF-composed portfolio strategies average returns are equal to zero. To test such a hypothesis one should perform t-tests with several significance levels. If the null hypothesis is rejected on a certain significance level, this would mean that the average return of the portfolio strategy is significantly different from the average return of the S&P500 index. Based on the results of the t-tests, one can conclude whether the above-mentioned market segment is inefficient or partially inefficient, which would mean one can find an "aggressive"strategy to secure stable above-market returns.